2009
DOI: 10.2169/internalmedicine.48.2569
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion-Related Acute Lung Injury (TRALI) Induced by Donor-Derived Anti-HLA Antibodies in Aplastic Anemia: Possible Priming Effect of Granulocyte-Colony Stimulating Factor (G-CSF) on the Recipient Neutrophils

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Neutrophil extracellular traps (NETs) consist of nuclear chromatin, hyper citrullinated histones, granular antimicrobial proteins and cytoplasmic proteins. In an ALI model of bacterial infection (Narayana Moorthy et al, 2013), LPS challenge (Tadie et al, 2013; Liu et al, 2016), transfusion (Hishizawa et al, 2009; Looney et al, 2009), and ventilation (Yildiz et al, 2015), NETs have been well documented, suggesting pivotal roles for NETs in ALI.…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophil extracellular traps (NETs) consist of nuclear chromatin, hyper citrullinated histones, granular antimicrobial proteins and cytoplasmic proteins. In an ALI model of bacterial infection (Narayana Moorthy et al, 2013), LPS challenge (Tadie et al, 2013; Liu et al, 2016), transfusion (Hishizawa et al, 2009; Looney et al, 2009), and ventilation (Yildiz et al, 2015), NETs have been well documented, suggesting pivotal roles for NETs in ALI.…”
Section: Introductionmentioning
confidence: 99%
“…Consensus definitions of TRALI have been developed but remain controversial. Similarly, in light of reports that granulocyte-colony-stimulating factor (G-CSF) might act as a neutrophil priming factor in predisposing patients for ALI (and possibly TRALI) [72][73][74][75], further research on the possible role of G-CSF in TRALI would be interesting. In addition, we need to better understand the pathophysiologic mechanisms that account for the overall worse outcomes of transfused critically ill patients, not necessarily attributable to ALI and respiratory compromise alone (e.g., immunomodulation and increased infection rates).…”
Section: Expert Commentary and Five-year Viewmentioning
confidence: 99%
“…Implicating factors for TRALI include white blood cell antibodies such as anti‐human leukocyte antigen (HLA) Class I and Class II, anti‐neutrophil antibodies, and soluble biologic molecules such as soluble CD40 ligand, lipids, or cytokines . In addition, we have previously reported that heme‐related molecules derived from hemolysis might also serve as an inducer of TRALI because hemin could activate neutrophils and produce ROS 17‐19.…”
mentioning
confidence: 99%